Comparison of effectiveness and safety between ceftriaxone/azithromycin and levofloxacin in hospitalized CAP patients: a review - Hikmah, Nurul; Andayani, Tri Murti; Puspitasari, Ika (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Community-acquired pneumonia (CAP) is a major health issue as it is a highly prevalent disease with significant morbidity and mortality worldwide. Current IDSA guidelines recommend ceftriaxone/azithromycin combination or levofloxacin monotheraphy as one of the empirical antibiotic options in non-ICU hospitalized CAP patients. This literature review aims to evaluate the comparative effectiveness and safety of ceftriaxone/azithromycin combination therapy and levofloxacin monotherapy in non-ICU hospitalized CAP patients. Four databases (PubMed, Scopus, DOAJ, and Cochrane Library) were used for article search with Boolean approach. Publication years were limited to 2013-2023 and without study design restrictions. Five articles which met the inclusion and exclusion criteria were evaluated. Two RCTs compared the effectiveness and safety of ceftriaxone/azithromycin combination and levofloxacin monotherapy, while the other 3 studies did not compare the safety of both antibiotic regimens due to the limitations of retrospective study design. The five studies analyzed the effectiveness of both regimens on various outcomes such as clinical improvement, mortality, and length of stay (LOS). The results of this literature review demonstrated that levofloxacin monotherapy had better clinical improvement, lower mortality, and reduced length of stay in non-ICU hospitalized CAP patients compared to ceftriaxone/azithromycin combination. However, the safety of both treatment regimens is still uncertain due to the limited number of studies evaluating the incidence of adverse events.